2015
DOI: 10.1016/j.freeradbiomed.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity training of mdx mice reduces carbonylation and increases expression levels of proteins involved in energy metabolism and muscle contraction

Abstract: High intensity training induces muscle damage in dystrophin-deficient mdx mice, an animal model for Duchenne muscular dystrophy. However, low intensity training (LIT) rescues the mdx phenotype and even reduces the level of protein carbonylation, a marker of oxidative damage. Until now, beneficial effects of LIT were mainly assessed at the physiological level. We investigated the effects of LIT at the molecular level on 8-week-old wild-type and mdx muscle using 2D Western blot and protein-protein interaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 60 publications
3
44
0
2
Order By: Relevance
“…weeks of low intensity swimming [10]. Differences in the age of animals, time point of animal euthanization following the last bout of exercise, exercise mode, intensity and volume, and in the basal redox status of mdx mice may explain these results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…weeks of low intensity swimming [10]. Differences in the age of animals, time point of animal euthanization following the last bout of exercise, exercise mode, intensity and volume, and in the basal redox status of mdx mice may explain these results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed increased oxidative stress as one candidate mechanism that may mediate the pathology of dystrophin deficiency [9,10]. Dystrophic mdx mice at the age of ~14 weeks showed significantly greater levels of oxidized glutathione (GSSG) (P<0.05) compared to healthy wild type animals ( Fig.…”
Section: Effects Of MDX Phenotype On Redox Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Further variables included the age of the mice and training duration. Voluntary and brief (<30 min per session) exercise of young mice (<8 weeks old) was defined as low intensity training [30, 59], whereas exercise of older mice, or under intensive or prolonged conditions (>30 min), was defined as high intensity training [63]. …”
Section: Experimental Procedures For the Study Of Exercise In MDX Micementioning
confidence: 99%